ETIKA NATURAL TAOISME DAN IMPLEMENTASINYA - Widisuseno, Iriyanto (HUMANIKA, 2016)
Ethical life according to Taoism means a way of life back to nature. Man must be able to interpret the laws of nature in an ethical perspective, and practice in the life of others. Taoism teaches life ethics need to be equipped virtue, which has a purity of heart that is sacred, or the sincerity and willingness to live for others. Taoist virtues law contains universal values, relevant for the people of Indonesia who are experiencing erosion and weakening of the appreciation of moral values. In addition, the transition period of political culture, especially from the time period of bureaucratic power to a democratic system of popular sovereignty towards civil society. Universal values of natural ethics Taoism in line with the ethical teachings of Pancasila.